2022
DOI: 10.1016/j.jad.2021.09.098
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of longitudinal cohort studies comparing mental health before versus during the COVID-19 pandemic in 2020

Abstract: Background Increases in mental health problems have been observed during the COVID-19 pandemic. The objectives were to examine the extent to which mental health symptoms changed during the pandemic in 2020, whether changes were persistent or short lived, and if changes were symptom specific. Methods Systematic review and meta-analysis of longitudinal cohort studies examining changes in mental health among the same group of participants before vs. during the pandemic in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

103
754
23
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 800 publications
(894 citation statements)
references
References 94 publications
103
754
23
14
Order By: Relevance
“…Even though the cross-sectional nature of the psychiatric data acquisition precludes the assessment of incidence rates, we were able to determine the prevalence of new psychiatric diagnoses. Our data indicate a high prevalence of new diagnoses of ‘depression’, ‘generalized anxiety disorder’ and ‘obsessive compulsive disorder’, contrasting with the findings of a recent meta-analysis of longitudinal studies that found only a small increase on mental health issues among general population pre- and post-COVID-19 pandemic [ 33 ]. Noteworthy, our sample is older and represented by COVID-19 survivors, and therefore more prone to be clinically impaired.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though the cross-sectional nature of the psychiatric data acquisition precludes the assessment of incidence rates, we were able to determine the prevalence of new psychiatric diagnoses. Our data indicate a high prevalence of new diagnoses of ‘depression’, ‘generalized anxiety disorder’ and ‘obsessive compulsive disorder’, contrasting with the findings of a recent meta-analysis of longitudinal studies that found only a small increase on mental health issues among general population pre- and post-COVID-19 pandemic [ 33 ]. Noteworthy, our sample is older and represented by COVID-19 survivors, and therefore more prone to be clinically impaired.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, based on statistics from pre-pandemic studies, several cross-sectional studies from China reported higher incidence rates for anxiety and depression symptoms in children and/or adolescents than expected [ 25 , 26 , 27 ]. Additionally, a longitudinal study of 14- to 17-year-old US adolescents also found increases in symptoms of depression and anxiety [ 28 ]. Similarly, an Australian study confirmed an increase in the incidence of severe symptoms of depression and anxiety in a sample of adolescents aged 13 to 16 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, people with poorer overall health tend to consider physical symptoms catastrophically and overestimate the risk of serious diseases, which may cause higher anxiety during pandemics [ 30 , 31 , 32 ]. The results also echoed with Robinson et al’s meta-analysis of longitudinal cohort studies, revealing that when comparing mental health symptoms to pre-pandemic levels, larger rises for depressive symptoms and those with existing poor physical health may have been most affected [ 14 ].…”
Section: Discussionmentioning
confidence: 80%
“…A meta-analysis of longitudinal cohort studies comparing mental health before versus during the COVID-19 pandemic in 2020 found an overall increase in mental health symptoms—e.g., [ 10 , 11 , 12 , 13 , 14 ]. Canet-Juric et al (2020) assessed the citizen’s emotional impact of the lockdown measures implemented by the Argentinian government to fight the COVID-19 pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%